A novel type of controlled low strength material derived from alum sludge and green materials. (20th March 2018) - Wang, Lei; Zou, Fuliao; Fang, Xiaoliang; Tsang, Daniel C.W.; Poon, Chi Sun; Leng, Zhen; Baek, Kitae
Graphical abstract: Highlights: Alum sludge can be recycled as fine aggregate into eco-friendly CLSM. Alum sludge addition increased water demand and hindered CH formation. PFA was a promising supplementary cementitious material for producing CLSM. Addition of CaCl2 or TEA effectively shortened overlong stiffening time. Abstract: The management and disposal of alum sludge generated from water treatment works is a worldwide issue. This study proposed an innovative method to utilize alum sludge as a partial replacement of recycled fine aggregate for producing controlled low strength material (CLSM). Various supplementary cementitious materials (SCMs) and accelerators were incorporated to produce CLSM with high flowability (>200 mm), relatively short stiffening time (<24 h), and moderate compressive strength (0.3–1 MPa). Cement chemistry and microstructure characteristics were evaluated by using isothermal calorimeter, quantitative X-ray diffraction, thermogravimetric analysis, and scanning electron microscopy analysis. The addition of alum sludge significantly increased water demand for maintaining sufficient flowability, resulting in long final stiffening time and low compressive strength. The high content of organic matter in alum sludge hampered the Ca(OH)2 formation and pH increase, thus delaying the induction period of cement hydration. The binder composition played an important role in the stiffening time of CLSM. Pulverized fly ash (PFA) was found to be the most effective SCM for improving flowability and adjusting compressive strength. Calcium-based accelerators or triethanolamine (TEA) significantly shortened the stiffening time to 7.4 h, which facilitated the samples to fulfill all the CLSM requirements. This study presents a new and eco-friendly approach to transform alum sludge into value-added construction materials in a sustainable way.